A Study of Polishing Feature of Ultrasonic-Assisted Vibration Method in Bamboo Charcoal - Hsin-Min Lee; Tzung-Ming Chen (Advances in Materials Science and Engineering)
Focusing on the feature of porosity in bamboo charcoal, this study applies the ultrasonic-assisted vibration method to perform surface polishing of the silicon wafer workpiece. The self-developed bamboo charcoal polishing spindle and ultrasonic- assisted vibration mechanism are attached to a single lapping machine. In the machining process, ultrasonic vibration enables the diamond slurry to smoothly pass through the microscopic holes of bamboo charcoal; the end of the bamboo charcoalis able to continue machining on the surface of the workpiece through the grasping force which exists in the microscopic holes. Under the polishing and machining parameters of ultrasonic-assisted vibration, with a diamond slurry concentration of 0.3%, the experimental results show a polishing time of 20 min, a loading of 25 N on the workpiece surface, a spindle speed of 1200 rpm, a vibration frequency of 30 kHz and the original surface roughness value of Ra 0.252 μm equals that of a mirror-like surface at Ra 0.017 μm. These research results prove that by using bamboo charcoal and ultrasonic-assisted vibration for polishing, a very good improvement can be achieved on the workpiece surface.